Physical chemistry - Laidler, Keith James; Meiser, John H. ([S.l.] : Houghton Mifflin Company, 1999)
With its clear explanations and practical pedagogy, Physical Chemistry is less intimidating to students than other texts, without sacrificing the mathematical rigor and comprehensiveness necessary for a junior-level physical chemistry course. The text's long-standing reputation for accessible writing provides clear instruction and superior problem-solving support for students.